1977
DOI: 10.1002/eji.1830071106
|View full text |Cite
|
Sign up to set email alerts
|

Secondary IgG responses to type 3 pneumococcal polysaccharide III. T cell requirement for development of B memory

Abstract: Mice primed with a thymus-dependent form of Type 3 pneumococcal polysaccharide (S3), i.e. S3 coupled to erythrocytes (S3-RBC) produces S3-specific IgG antibody after secondary challenge with S3-RBC. When mice are depleted of T cells by treatment with anti-lymphocyte serum (ALS) at the time of priming, no IgG antibody is produced after secondary challenge. In order to determine the cellular basis for this phenomenon, various combinations of T and/or B cells from ALS-treated or normal primed mice were transferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Although it is well established that Th1 effector CD4ϩ T cells are required for the control of parasitemia early in primary P. c. chabaudi infection (19), these data suggest that inflammatory CD4 ϩ T-cell responses are unlikely to contribute significantly to protection against repeat infection. In contrast, antibody boosting during challenge in patently infected mice (results not shown) suggested that antibody responses were preserved, consistent with the reduced requirements for CD4ϩ T-cell help during secondary antibody responses (1,35).…”
Section: Discussionmentioning
confidence: 60%
“…Although it is well established that Th1 effector CD4ϩ T cells are required for the control of parasitemia early in primary P. c. chabaudi infection (19), these data suggest that inflammatory CD4 ϩ T-cell responses are unlikely to contribute significantly to protection against repeat infection. In contrast, antibody boosting during challenge in patently infected mice (results not shown) suggested that antibody responses were preserved, consistent with the reduced requirements for CD4ϩ T-cell help during secondary antibody responses (1,35).…”
Section: Discussionmentioning
confidence: 60%
“…2 compared with that shown in Fig. 1 most likely resulted from the longer interval between primary and secondary immunization in the second experiment (70 versus 47 days), as extending the interval between the two injections has been shown to increase the secondary response to PPS conjugate vaccines (1).…”
Section: Vol 69 2001mentioning
confidence: 86%
“…The finding that all the clones expressed after the conjugate vaccine were restimulated by CP suggests that, functionally, only one type of memory cell exists after multiple immunization with a conjugate vaccine, and it is a memory cell responsive to CP. We do not know whether the precursor cell induced by the conjugate to respond to CP initially belonged to a potentially CPresponsive subset and has the ability to respond to a TD form of the antigen earlier in ontogeny than to the isolated CP, or belonged to a subset that would normally be unresponsive or easily tolerized to the CP (11,16,17), and with exposure to the conjugate vaccine has become CP-responsive. A precedent for the former possibility has been described (16) in the earlier development, in mice, of an antidextran antibody response to immunization with isomaltohexaose coupled to KLH than to immunization with dextran itself.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…The antibody response in mice and rabbits to immunization with the H. influenzae b CP is poor, whether administered either as a primary vaccine or as a secondary vaccine after priming with either conjugate vaccines or killed bacteria (2,7,8, and our unpublished observations). In contrast, immunization of rabbits and mice with killed pneumococci or TD forms of pneumococcal CP can prime for secondary responses to the isolated CP (18)(19)(20)(21). However, the secondary response to the isolated CP is not produced until fairly long after primary immunization (19), and is produced later than observed for secondary responses to TD forms of the CP (21).…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%